Os caminhos do desenvolvimento e o crescimento da forma urbana de Campo Mourão-PR, da década de 1940 a 1970 - Batista, Marinalva dos Reis (2014)
The objective of this dissertation is to analyze and discuss the ways of the development and growth of the urban form of Campo Mourão-PR; focusing on agents and the urban legislation that participate of this process. The research about Campo Mourão aims to present a geographic-historic synthesis between the decades of 1940 and 1970. For this understanding of the city, we highlighted Milton's Method of analysis of space - that seeks to understand the spatial organization across the categories: structure, function, form and process - with considerations about urban spatial organization, comprehending the producing agents from urban space. Moreover, we look up to discuss the municipality, through the main achievements of municipal management and urban planning laws, that also aim to spatial organization as well as the other laws that are guiding the structuring of the city. In this research, the landscape was thought as the dialectical relationship between the categories of analysis of Milton Santos. Until the 1950s, the state acts with greater force on the installment plan, even as the city is being created. In the 1960s, a big upset occurs; there is the massive investment of the middle class lunched urban sprawl, even in the later decades. In the agricultural environment, especially in the 1960s, the main function of the municipality was to provide wood for the state. In the 1970s, we see the change in this function. The municipality starts producing grains, the same way as many of the municipalities of Paraná. The economic dynamics and structure of the city as the regional hub also started to highlight itself in the tertiary and the secondary sector as explicit data. And it even took control of agricultural production in their region further with the founding of the Cooperative Coamo. We can consider that if this change had not occurred in the function of Campo Mourão being a country town, it would not have the importance it has today in the northern cities of Paraná network, especially for its geographic micro region. The structure of Campo Mourão in the late 1970s is similar to the most developed cities in the north of Paraná; showing strong economic activities in the countryside or in the city. Although still nascent, it closes a cycle of consolidation of the urban core, that will serve as the base for a future development